THE FINAL ANALYSIS: 10-YEAR TREATMENT RESULTS OF ACUTE LYMPHOBLASTIC LEUKEMIA IN CHILDREN OF SAINT-PETERSBURG ON THE PROTOCOL COALL-92-SAINT-PETERSBURG - E.G. Boichenko (Union of pediatricians of Russia, 2010)
The article demonstrates the treatment results on the protocol the treatment of children with acute lymphoblastic leukemia (ALL) (COALL-92-Saint-Petersburg) after 10 years of follow-up. Between January, 1999 and August, 2008, a total of 272 children and adolescents 0-18 yr of age, from Saint-Petersburg and its area were eligible for the protocol. All the patients have met diagnostic criteria for ALL. Those with a mature B-cell phenotype and FAB-L3 morphology were excluded. The diagnosis was based on morphological evaluation of the peripheral blood and bone marrow smears, immunophenotyping and cytogenetic analysis. All patients were classified as being at lower (LR, 47%) or higher (HR, 53%) risk of relapse. The intensive phase of treatment lasted 5, 5 months in low risk group and 8 months in high risk group and consisted of 4 parts (induction, consolidation, CNS-treatment and reinduction). It was followed by maintenance treatment until 2 years from date of diagnosis. After an observation time of 11 years, the estimate for EFS of all 272 evaluable patients was 67,7 ± 3,1%, the estimate of probability of RFS was 74,1 ± 3,3%, and probability of overall survival was 75,6 ± 3,0%. Key words: acute lymphoblastic leukemia, intensive chemotherapy, children. (Pediatric Pharmacology. - 2010; 7(6):50-56)